ANALISIS MODEL KEBUTUHAN PERGERAKAN PENUMPANG DAN BARANG BANDARA RAHADI OESMAN KETAPANG - Elsa Trimukti, . (Fakultas Teknik Universitas Tanjungpura, 2010)
Airport of Rahadi Oesman in Kabupaten Ketapang Kalimantan Barat represent the main and important gate for air transport in Kabupaten Ketapang, where this airport own the strategic role in service activities of this transportation even for domestic transportation or regional. Activity in Airport of Rahadi Oesman in a few this the last year has growth so fast growth, so that felt the infrastructure and also available facility in this time have is not adequate again to support the growth rate of air traffic in this airport. In the plan development of facility of air side and also land side of the airport require to be conducted an analysis model of trip generation or attraction of passenger and goods. These models need for the prediction of mount the growth of passenger and goods/cargo and estimate the amount of passenger and aircraft movement in the future pursuant to aircraft characteristic that to be used. The models used for prediction of passenger and goods in this study are Trend Analysis Models consisted of linear regression trend method, exponential regression trend method, and polynomial regression trend method. Besides model of trend analysis, in this study also analyzed Market Share Model. Result from third model then compared to one another to obtain the most appropriate model. Pursuant to analyses result obtained that the best or most appropriate model is Model of Trend Analysis.Model for the attraction passenger is Y = 21,18X2+ 6181X + 5788 by R2= 0,922.Model for the generation passenger is Y = 128,3X2+ 7515X + 4965 by R2= 0,907.Model for the passenger of transit is Y = 795X2+ 561X + 3361 by R2= 1Model for the cargo movement is Y = 2468X2+ 41054X 28341 by R2= 0,918.